Prognostic impact of serum albumin levels on the recurrence of stage I non-small cell lung cancer (Clinics, 2013)
Objective: Patients with stage I non-small cell lung cancer who have undergone complete surgical resection harbor a 30% risk for tumor recurrence. Thus, the identification of factors that are predictive for tumor recurrence is urgently needed. The aim of this study was to test the prognostic value of serum albumin levels on tumor recurrence in patients with stage I non-small cell lung cancer. Methods: Stage I non-small cell lung cancer patients who underwent complete surgical resection of the primary tumor at Zhejiang Hospital were analyzed in this study. Serum albumin levels were measured before surgery and once again after surgery in 101 histologically diagnosed non-small cell lung cancer patients. Correlations between the pre- and post-operative serum albumin levels and various clinical demographics and recurrence-free survival rates were analyzed. Results: Patients with pre-operative hypoalbuminemia (